2012
DOI: 10.1177/0954409712445114
|View full text |Cite
|
Sign up to set email alerts
|

Rail vehicle passing through a turnout: analysis of different turnout designs and wheel profiles

Abstract: In recent years, different systems have been developed in order to improve the dynamic behaviour of railway vehicles when passing through turnouts. Some of these improvements consist in varying the geometry of the switch itself and including moveable crossing vees. It is worth mentioning that they are designed by taking a certain wheel profile into consideration, i.e. it is assumed that the wheel profile does not change.The objective of the current study is to determine the influence that the turnout design ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…MBS tool dedicated for train-track analysis has a wheel-rail contact module that is able to model complex wheel-rail kinematic behaviour and the corresponding creep forces. Some authors, for example, Kassa and Nielsen [6], Lagos et al [7], Wan et al [8], Pålsson [9], and Lau and Kassa [10], used MBS to simulate trainturnout dynamic interaction to evaluate the maximum contact forces along a railway turnout, to study the influence of the turnout geometry, to optimise crossing nose profile, to optimise switch geometry, and to study the effect of yaw in a switch and crossing, respectively. As reported by Esveld [11], the track substructure has a direct influence on the dynamic wheel load, dynamic track stiffness, and track roughness.…”
Section: Introductionmentioning
confidence: 99%
“…MBS tool dedicated for train-track analysis has a wheel-rail contact module that is able to model complex wheel-rail kinematic behaviour and the corresponding creep forces. Some authors, for example, Kassa and Nielsen [6], Lagos et al [7], Wan et al [8], Pålsson [9], and Lau and Kassa [10], used MBS to simulate trainturnout dynamic interaction to evaluate the maximum contact forces along a railway turnout, to study the influence of the turnout geometry, to optimise crossing nose profile, to optimise switch geometry, and to study the effect of yaw in a switch and crossing, respectively. As reported by Esveld [11], the track substructure has a direct influence on the dynamic wheel load, dynamic track stiffness, and track roughness.…”
Section: Introductionmentioning
confidence: 99%
“…It was acknowledged at the start of the project that simulation methods for vehicle dynamic interaction at switches and crossings either based on available multibody system tools (Andersson et al, 2006, Lagos et al, 2012, Nicklisch et al, 2010 or more complex FE models (Markine et al, 2011, Pletz et al, 2012, Wan et al, 2014 have been used very successfully but are generally complex and time consuming, thus limiting the quantity of cases which can be simulated. This is particularly true with wheel population investigated, which constitute a significant contributor to the variation in predicted results.…”
Section: Methodology and Numerical Toolsmentioning
confidence: 99%
“…With regard to the research status about switch panel, there is not much relevant investigation until now. Currently, most of the employed model is based on multibody system (MBS) . Thanks to its computational efficiency, the influence of parameter variation is readily to be examined by MBS.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, dynamic contact force is adopted to evaluate the damage on these defect-like components. [9][10][11][12][13][14] However, according to the previous study, 5 it is found that fatigue initiation spot is the birthplace of these bites. This detection suggests that multiaxial fatigue criterion could be more appropriate for damage evaluation on switch blade, instead of using dynamic contact force.…”
Section: Introductionmentioning
confidence: 99%